Prospectus Institut Teknologi MARA 1990-1991 / Public Relations Unit, ITM - Public Relations Unit, ITM (Public Relations Unit, ITM, 1990)
Institut Teknologi MARA (ITM) is a unique institution of higher learning and was established to fulfil two main objectives. These were to provide opportunities for Bumiputras from the rural areas to obtain education at the tertiary level and to provide hands-on experience for them in the various professional and semi professional fields. Our mission is to be the best Institution of higher learning in Malaysia as well as to achieve academic excellence in the fields of science, technology, business and management in accordance with national needs.